Restore Public Trust Through Deliberative Public Policy Formulation - Mardiyanta, Antun (UI Scholars Hub, 2013)
Public trust is a very essential and fundamental element to the legitimacy of public administration. Moreover, the local government is obliged to serve the community. Without public trust, many policies may have serious problems. Therefore, it is necessary to maintain and enhance public trust. A highly committed public trust will allow public administrators to receive good judgment, which is, necessary in the policy-making process. This paper is carefully seeing through some findings of a deliberative public policy formulation, especially in the planning and budgeting areas. The qualitative study was conducted in the Probolinggo regency from 2008 to early 2011. Data were collected through participant and non-participant observation, focus group discussions, in-depth interviews, as well as search of relevant documents. The findings of this study indicate the existence of change in public which in the current situation requires a commitment of local political elite to open public places. Commitment to the use of public places, in the application of the transparency principles, participation and accountability in public policy formulation process, will bring back public trust to the local government; especially if the local society feels and believes that the deliberative public participation will significantly affect the final result of the policy formulation.